2011
DOI: 10.4103/0019-5413.83140
|View full text |Cite
|
Sign up to set email alerts
|

Spinaplasty following lumbar laminectomy for multilevel lumbar spinal stenosis to prevent iatrogenic instability

Abstract: Background:Iatrogenic instability following laminectomy occurs in patients with degenerative lumbar canal stenosis. Long segment fusions to obviate postoperative instability result in loss of motion of lumbar spine and predisposes to adjacent level degeneration. The best alternative would be an adequate decompressive laminectomy with a nonfusion technique of preserving the posterior ligament complex integrity. We report a retrospective analysis of multilevel lumbar canal stenosis that were operated for posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This innovative laminoplasty restored the integrity of the posterior tension band, and good results were obtained during follow-up. 37 Kim et al 38 also demonstrated that similar lamina reconstruction could better preserve the segmental stability using FE analysis. Lee et al 25 found that either proximal screw-rod-based hybrid stabilization or interspinous device-based hybrid stabilization can provide a transition zone of activity in the proximal region, limiting excessive ROM and intradiscal stress increase in the adjacent segment.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative laminoplasty restored the integrity of the posterior tension band, and good results were obtained during follow-up. 37 Kim et al 38 also demonstrated that similar lamina reconstruction could better preserve the segmental stability using FE analysis. Lee et al 25 found that either proximal screw-rod-based hybrid stabilization or interspinous device-based hybrid stabilization can provide a transition zone of activity in the proximal region, limiting excessive ROM and intradiscal stress increase in the adjacent segment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent the formation of hematoma and scar tissue, several laminoplasty have been carried out for LSS. [ 16 ] Restorative laminoplasty was also reported. However, it is difficult to restore the excised laminae precisely.…”
Section: Introductionmentioning
confidence: 99%
“…However, too limited a decompression can be accompanied by re-growth of the bone that affects the long term results. The best option would be an adequate decompressive limited laminectomy with a nonfusion technique of preserving the posterior ligament complex integrity [ 11 ]. The integrity of the posterior ligament complex (spinous process, intraspinous ligaments and supraspinous ligaments) and paraspinal muscles minimizes the risk of developing de novo postoperative spinal instability.…”
Section: Introductionmentioning
confidence: 99%